Transfer of basic science knowledge in a problem‐based learning curriculum. (13th May 2020) - Ali, Kamran; Cockerill, Josephine; Bennett, Jon H.; Belfield, Louise; Tredwin, Christopher
Abstract: Aim: The aim of this study was to evaluate transfer of basic science knowledge for clinical application in our BDS programme by exploring the correlations between student performance in integrated dental science (IDS) examinations and applied dental knowledge (ADK) tests. Methods: Numeric test scores were drawn from summative IDS and ADK assessments undertaken by BDS students spanning six academic years (2013‐14 to 2018‐19) for two cohorts (2013 and 2014). The data included a total of 13 test scores for each cohort with four IDS tests, taken in Years 1 and 2, and nine ADK tests taken in Years 3, 4 and 5. Results: The sample included 120 students across both cohorts with 65 females (54%) and 55 males (46%). The correlation coefficients between the successive tests and the combinations of IDS and ADK scores were positive, all being greater than 0.48, and all being significantly correlated ( P  < .001). Regarding correlation between standardised averages across all IDS tests and all ADK tests, performance remained significantly correlated: (2013 cohort: r (53) = .667, P  < .001; 2014 cohort: r (50) = .700, P  < .001). Conclusions: The results of this study show that the students' knowledge of basic sciences correlates with their applied dental knowledge and may offer a predictive value. These findings may be attributed to a PBL curriculum and student‐led learning at our school.